Design of Gradual Contemporary Wayang Visual Character Indonesia For Sticker Chatting And Game Applications - James Darmawan; Irwan Harnoko (Journal of Games, Game Art, and Gamification, 2017)
UNESCO international recognition in 2003 stated that wayang is one of Indonesia's cultural heritage, but the sense of belonging for wayang is still low among the nation's next generation of Indonesia. So at this time, both the government and the educators, still working to improve the regeneration of wayang knowledge and recognition for the young nation and the world, including through game application. In this study, the researchers created a contemporary virtual character of wayang, and will be inserted as a character sticker chatting and game application. This wayang virtual characters can be used as tools for reintroduction to young people around the world. This method will be conducted by researchers include depictions classification of facial expressions of emotion, collaborate with simplified visual approach, to obtain the corresponding visual characteristics of the wayang virtual characters. Researchers also used visual basic character as a prototype for contemporary form deformation, so it can be applied to the target games application and communication functions.